2021
DOI: 10.48550/arxiv.2102.11569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Challenges Ahead for Multimessenger Analyses of Gravitational Waves and Kilonova: a Case Study on GW190425

Geert Raaijmakers,
Samaya Nissanke,
Francois Foucart
et al.

Abstract: In recent years, there have been significant advances in multi-messenger astronomy due to the discovery of the first, and so far only confirmed, gravitational wave event with a simultaneous electromagnetic (EM) counterpart, as well as improvements in numerical simulations, gravitational wave (GW) detectors, and transient astronomy. This has led to the exciting possibility of performing joint analyses of the GW and EM data, providing additional constraints on fundamental properties of the binary progenitor and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…It has been suggested that due to their faintness and fast evolution, searches by optical surveys for kilonovae within a distance up to 200 Mpc require early observations down to magnitude 21 [554]. Future counterpart detections as soon as the next observing run are likely to place strong, multimessenger constraints on the equation of state of NSs, and the Hubble constant [555][556][557][558][559].…”
Section: Appendix A: Low-latency Alert System and Multimessenger Foll...mentioning
confidence: 99%
“…It has been suggested that due to their faintness and fast evolution, searches by optical surveys for kilonovae within a distance up to 200 Mpc require early observations down to magnitude 21 [554]. Future counterpart detections as soon as the next observing run are likely to place strong, multimessenger constraints on the equation of state of NSs, and the Hubble constant [555][556][557][558][559].…”
Section: Appendix A: Low-latency Alert System and Multimessenger Foll...mentioning
confidence: 99%
“…Here we analyze the bolometric luminosity of GW170817 (as compiled in Kasliwal et al 2017) via the new Bayesian framework outlined in Raaijmakers et al (2021b). We consider a two-component kilonova model, where the first component, the dynamical ejecta, is associated with material ejected through tidal forces and the shock interface between the two neutron stars (see, e.g., Radice et al 2018, and references therein).…”
Section: At2017gfomentioning
confidence: 99%
“…Nevertheless, uncertainties in the numerical simulations used to model these outflows, in the properties of the elements produced during the r-process, and in the heating rate of the ejecta due to radioactive decays create significant difficulties when attempting to interpret kilonovae signals, with highly uncertain error bars in any inference made about the parameters of the merging compact objects (see e.g. [40][41][42]).…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the properties of matter outflows in NSNS and BHNS mergers is crucial to our ability to perform detailed analysis of kilonovae. Such predictions are typically made by developing analytical fits to the results of merger and post-merger simulations of these systems [42][43][44][45][46][47]. A reliable determination of the properties of unbound material in merger simulations is accordingly important to kilonova modeling efforts.…”
Section: Introductionmentioning
confidence: 99%